2004 IEEE International Conference on Systems, Man and Cybernetics (IEEE Cat. No.04CH37583)
DOI: 10.1109/icsmc.2004.1398273
|View full text |Cite
|
Sign up to set email alerts
|

Interrupting people at home

Abstract: Several factors were examined towardsconsidering what influences users' acceptability of alerfing and informational messages in a field study conducted at fen homes. Through the simulation study message urgency was found to be a better predictor of acceptability than the degree of user engagement during ongoing activities. A model is proposedfor including a range of additional factors expected to influence acceptahility. The factors will be examined in forthcoming studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 4 publications
0
10
1
Order By: Relevance
“…Based on the results of the pilot study [22], this dominating effect of message urgency was expected. Whereas the effect of user engagement in activities was not clear in the pilot study, the present study does show that acceptability of low-urgent and medium-urgent messages may be improved by creating a system that is aware of user activities, and that adapts the presentation and timing to the activity context.…”
Section: General Acceptabilitymentioning
confidence: 94%
See 3 more Smart Citations
“…Based on the results of the pilot study [22], this dominating effect of message urgency was expected. Whereas the effect of user engagement in activities was not clear in the pilot study, the present study does show that acceptability of low-urgent and medium-urgent messages may be improved by creating a system that is aware of user activities, and that adapts the presentation and timing to the activity context.…”
Section: General Acceptabilitymentioning
confidence: 94%
“…In a previous experiment by Vastenburg et al [22], which served as a pilot for the present study, subjective data were collected and analyzed in an exploratory field study. For each inflicted interruption, participants were asked to describe their activities, rate their state and context, and judge the value and urgency of the notification messages as well as the acceptability of the interruptions.…”
Section: Notifications In the Homementioning
confidence: 99%
See 2 more Smart Citations
“…For example, the identity of a notifications sender has been shown to be an important consideration for the recipient's receptivity and responsiveness [13], [14]. Further, a number of empirical studies have found that if the content of the notification is perceived as urgent [15], relevant [16], and/or complex [17] responsiveness can change. This can also be influenced by the way an interruption is presented, for example if the notification is delivered directly to the screen (an immediate interruption), or if the user needs to accept the notification first (a negotiated interruption) [18].…”
Section: B Relational Context Factorsmentioning
confidence: 99%